PEMBELAJARAN GITAR ELEKTRIK METAL DI PROGRAM AGC MUSIC SCHOOL - Galih Wahyu Permana, - (2019)
This research is titled Metal Electric Guitar Learning in the AGC Music School Program. This research was conducted to describe the learning of Metal electric guitar at AGC Music School which contains an electric guitar that is supported by the amplification component as a medium of Metal electric guitar learning at AGC Music School and how to use training patterns in learning Metal electric guitar at AGC Music School. This research also aims to increase the reader's knowledge about the complexity of the electric guitar in terms of instrumentation and amplification systems, as well as applications in Metal music. In this study the method used is a qualitative research method through descriptive analysis research, with the aim of providing an assessment of data analysis obtained systematically and accurately. The data obtained through direct observation during learning, through direct research with informants and informants in the form of interviews, as well as data such as audio, video, literature and other documentation, so as to provide a clear picture of learning metal electric guitar at AGC Music School. The data findings from this study are that Metal music is identical to the high-gain sound produced through its amplification device. In learning Metal electric guitar at AGC Music School, the learning media used are electric guitars using humbucker pickups. Because the pickup humbucker is able to produce heavy and thick sound characters, and can receive high-gain sound well. In addition, there is also a set of electric guitar amplifiers that are used as a medium to get the required distortion sound effect capacity through the settings on the pre-amp. and get information about the application of training pattern material focused on the right and left hand playing techniques to improve endurance, durability, power and accuracy so that it can produce maximum tones in guitar playing supported by high-gain sound. Keywords: Electric Learning, Guitar, Heavy Metal Music, AGC Music School